Cloning and molecular characterization of fibronectin attachment protein gene (ModD) of Mycobacterium avium subspecies paratuberculosis - GARG, AKSHAY; VERMA, RISHENDRA (The Indian Journal of Animal Sciences, 2017)
Fibronectin attachment protein (FAP) also known as ModD gene of 987 bp size was identified in the Mycobacterium avium subsp. paratuberculosis (MAP) genome. This gene was successfully amplified by PCR using specific primers and MAP genomic DNA template, in the presence of 10% DMSO and glycerol. The PCR product was cloned in pGEMT easy cloning vector and subsequently subcloned into pET-33b expression vector and sequenced. MAP ModD gene showed sequence identity ranging from 64 to 94% at nucleotide level and 47-87% at amino acid level, by WU-BLAST program with FAPs of other Mycobacteria species. MAP ModD gene showed 97% sequence homology with M. avium subsp avium ModD by Megalign tool of DNAStar programme. This strong identity was attributed to the more close genetic association of these two species. MAP ModD protein is mainly composed of beta sheets and is highly antigenic. Positive pETModD recombinant clone was induced with IPTG for expression of the ModD protein. The MAP ModD protein was purified under native condition using nickel affinity column. The expressed recombinant ModD (52 kDa) was confirmed by Western blot with nickel-HRPO conjugate and rabbit hyperimmune serum raised against recombinant ModD.